Post Mid‐Cretaceous Tectonic and Topographic Evolution of Western Marie Byrd Land, WestAntarctica: Insights from Apatite FissionTrack and (U‐Th‐Sm)/He Data. (6th December 2019) - Zundel, Maximilian; Spiegel, Cornelia; Lisker, Frank; Monien, Patrick
Key Points: This study reports the first apatite (U‐Th‐Sm)/He data from western Marie Byrd Land Thermal history modeling indicates diachronous Late Cretaceous‐Paleogene cooling in response to different tectonic processes Erosion surfaces in West Antarctica formed diachronously from west to east after 70 Ma Abstract: New low‐temperature thermochronological data from granitic basement of western Marie Byrd Land (MBL) provide insights into the still poorly constrained tectonic and topographic evolution of West Antarctica during and after continental breakup. Here, we present the first apatite (U‐Th‐Sm)/He data from the Devonian Ford Granodiorite and the mid‐Cretaceous Byrd Coast Granite suites from the Ford Ranges and the Edward VII Peninsula. Thermal history modeling integrating apatite (U‐Th‐Sm)/He dates of 109–68 Ma with revised apatite fission track data in combination with geologic information indicates a thermal history with diachronous enhanced cooling at 100–60 Ma and subsequent slow cooling until the present day. Enhanced cooling at 100–70 Ma was related to activity of the West Antarctic rift system and to continental breakup, thereby exhuming most samples to shallow crustal levels. Localized cooling at 75–60 Ma is interpreted as resulting from faulting in the eastern Ross Sea region. Slow cooling after 70–60 Ma corresponds with formation of erosion surfaces in western MBL. Comparison of our results from western MBL with data from the literature indicates progressive formation of erosion surfaces from west to east along the MBL‐Thurston Island crustal blocks. Late Cenozoic activity of the West Antarctic rift system and MBL dome uplift appear to have caused only minor exhumation of <1.5 km in western MBL.